Absolute Quantitation of MDR1 Transcripts Using Heterologous DNA Standards—Validation of the Competitive RT-PCR (CRT-PCR) Approach. (June 1999) - El-Osta, Assam; Kantharidis, Phillip; Zalcberg, John
The multidrug resistance ( MDR1 ) gene product, P-glycoprotein (Pgp), is a 170-kDa ATP-dependent pump that expels a variety of anticancer drugs out of malignant cells, reducing drug accumulation and thus antitumor activity. In recent years, considerable data has been presented that indicates the need to standardize detection methods for Pgp and MDR1 . Reverse transcription (RT)-PCR is one of the most sensitive and specific techniques used to detect MDR1 . Nevertheless, there is the need to address working criteria for quantitation by RT-PCR. In this study, we describe a flexible assay used to quantify MDR1 gene expression using heterologous (nonhomologous) standards for use in competitive RT-PCR (CRT-PCR). Our guidelines were to use a RT-PCR quantitation method that was independent of exponential phase kinetics, sensitive (detect low levels of gene measurement in clinical samples) and did not require radiolabel. Furthermore, the method would need to be flexible enough for the user to express quantitation as either the number of cells or amount of cDNA used in CRT-PCR. Using low-stringency amplification, heterologous DNA competitors were constructed for MDR1 and as an internal reference, the ubiquitously expressed human histone variant 3.3 (H3.3). The benefits of this approach are threefold: (i) amplification kinetics of target and competitor molecules are identical, (ii) low-stringency PCR is a simple way of constructing heterologous DNA competitors that do not require special storage conditions and (iii) heterologous competitors avoid the formation of heteroduplex molecules. We conclude that CRT-PCR is an extremely flexible and sensitive assay that can quantify MDR1 based on competitive amplification of a heterologous competitor. This might complement future efforts to standardize MDR1 detection methods using RT-PCR.